Palm oil mill final discharge treatment by a continuous adsorption system using oil palm kernel shell activated carbon produced from two-in-one carbonization activation reactor system - Z., Nahrul Hayawin; M.F., Ibrahim; J., Nor Faizah; M., Ropandi; A.A., Astimar; Abd-Aziz, Suraini (Elsevier, 2020)
This work aimed at removing a major amount of organic and inorganic pollutants existing in palm oil mill effluent (POME) final discharge by using an effective adsorbent from renewable sources. In this study, the treatment of effluent by a continuous system that had improved the removal efficiency as compared to the previous batch system is demonstrated. The renewable sources of oil palm kernel shell activated carbon (ACOPKS) has been produced using a two-in-one carbonization activation system, packed into a column for continuous adsorption system to reduce the concentration of biological oxygen demand (BOD), chemical oxygen demand (COD), total suspended solids (TSS) and colour intensity of the palm oil mill effluent (POME) final discharge. The continuous adsorption system was tested using AC-OPKS dosages of 0.01–0.05 kg L−1 at a constant pH of 8.03 with different treatment times of 2–12 h and flow rates of 30–70 mL min−1 to determine the optimal adsorbent capacity. It was found that the optimal dosage of 0.04 kg L−1 , the flow rate of 50 mL min−1 and a treatment time of 10 h gave the highest adsorption capacity. In comparison with the batch system, this continuous adsorption system had improved the reduction of BOD, COD, TSS and colour intensity from 90 %, 68 %, 97 % and 83 % (using a batch system) to 93.52 %, 92.79 %, 94.84 % and 89.21 %, respectively (using a continuous system). The treated POME final discharge has the BOD value of 19.10 mg L−1 , which is below than the standard set (20 mg L−1 ) by the Department of Environment Malaysia (DOE) under the Environmental Quality Act 1974